Identification and molecular characterization of CD4 genes in brown trout (Salmo trutta). (June 2020) - Ashfaq, Hassan; El-Matbouli, Mansour; Soliman, Hatem
Abstract: CD4 + cells are vital in coordinating the immune response against pathogens. In the present study, three different CD4 homologs, namely, CD4-1, CD4-2a, and CD4-2b were identified and characterized. Further, their basal expression levels in different brown trout ( Salmo trutta ) tissues were also investigated. CD4-1 was 1473 nucleotides long, with an open reading frame (ORF) encoding 490 amino acids with four immunoglobulin superfamily-like domains. CD4-2a and CD4-2b like genes were 945 and 999 nucleotides long containing ORFs with 313 and 331 amino acids, respectively. The brown trout CD4-1 protein sequence demonstrated a 95% and 89% identity with Atlantic salmon and rainbow trout CD4-1 genes, respectively. On the other hand, brown trout CD4-2a and CD4-2b protein sequences presented an identity of 84% and 97.7% with rainbow trout and Atlantic salmon, respectively. The basal expression levels of the identified brown trout CD4-genes were investigated, which were higher in thymus, spleen, and head kidney than in those the gills, liver, intestine, heart, and brain tissues. Highlights: Three different CD4 homologs were identified from brown trout. Sequences of these genes demonstrated high percent of identity to other fish species. Basal expression of these genes is higher in lymphoid organs than non-lymphoid organs.